Difference between revisions of "1993 USAMO Problems/Problem 1"
(→Solution) |
(→Solution) |
||
Line 19: | Line 19: | ||
a^{2n}-a&>b^{2n}-b \tag{5} | a^{2n}-a&>b^{2n}-b \tag{5} | ||
\end{align*}</cmath> | \end{align*}</cmath> | ||
− | where we substituted in equations (1) and (2) to achieve (5). Notice that from <math>a^{2n}=a+1</math> we have <math>a>1</math>. Thus, if <math>b>a</math>, then <math>b^{2n-1}-1>a^{2n-1}-1. Since < | + | where we substituted in equations (1) and (2) to achieve (5). Notice that from <math>a^{2n}=a+1</math> we have <math>a>1</math>. Thus, if <math>b>a</math>, then <math>b^{2n-1}-1>a^{2n-1}-1</math>. Since <math>a>1\Rightarrow a^{2n-1}-1>0</math>, multiplying the two inequalities yields <math>b^{2n}-b>a^{2n}-a</math>, a contradiction, so <math>a> b</math>. However, when <math>n</math> equals <math>0</math> or <math>1</math>, the first equation becomes meaningless, so we conclude that for each integer <math>n\ge 2</math>, we always have <math>a>b</math>. |
== See also == | == See also == |
Revision as of 17:25, 10 November 2008
Problem
For each integer , determine, with proof, which of the two positive real numbers
and
satisfying
is larger.
Solution
Square and rearrange the first equation and also rearrange the second.
It is trivial that
since
clearly cannot equal
(Otherwise
). Thus
where we substituted in equations (1) and (2) to achieve (5). Notice that from
we have
. Thus, if
, then
. Since
, multiplying the two inequalities yields
, a contradiction, so
. However, when
equals
or
, the first equation becomes meaningless, so we conclude that for each integer
, we always have
.
See also
1993 USAMO (Problems • Resources) | ||
Preceded by First question |
Followed by Problem 2 | |
1 • 2 • 3 • 4 • 5 | ||
All USAMO Problems and Solutions |